2020
DOI: 10.1186/s12876-020-01436-3
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal papillary mucinous neoplasm complicated with intraductal bleeding in a young woman mimicked a cystic solid pseudo-papillary tumor: a case report

Abstract: Background There are only 6 cases of intraductal papillary mucinous neoplasm (IPMN) complicated with intraductal hemorrhage have been reported in English literatures. All these 6 cases of IPMN occurred in the old people. The present rare case of IPMN complicated with intraductal hemorrhage occurred in a young woman, and mimicked a cystic solid pseudo-papillary neoplasm (SPN) on preoperative imaging findings. Case presentation A 29-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Both age and metabolic syndrome increase the occurrence of IPMNs[ 18 ]. Acute pancreatitis predicts malignancy and constitutes an indication for pancreatectomy[ 19 ]. High-risk stigmata and worrisome features may predict malignant transformation in clinical practice and determine management policy, as shown in Table 1 [ 3 , 20 ].…”
Section: To the Editormentioning
confidence: 99%
“…Both age and metabolic syndrome increase the occurrence of IPMNs[ 18 ]. Acute pancreatitis predicts malignancy and constitutes an indication for pancreatectomy[ 19 ]. High-risk stigmata and worrisome features may predict malignant transformation in clinical practice and determine management policy, as shown in Table 1 [ 3 , 20 ].…”
Section: To the Editormentioning
confidence: 99%
“…A retrospective study including 132 cases of definitely radiologically diagnosed SPN indicated that the overall diagnosis rate was 78.5% for CT and 77.8% for MRI [ 31 ]. MRCP result is able to show communication between the lesion and the tumor but has limitations when focusing on recognizing malignant SPNs [ 32 ].…”
Section: Identification and Assessment Of Spn Malignancymentioning
confidence: 99%